Comparison of endotracheal intubation between c-mac video laryngoscope and airtraq device - M. Raghupraveen Kumar; P.V.S.Lavanya; M.Venkata Ganesh; T.Swathi Priyadarshini; T.Chandana Krishna (International Journal of Health and Clinical Research, 2021)
Background: Failed tracheal intubation is the leading cause of anesthetic morbidity and mortality both within and outside the operation theatre. To determine intubation difficulty, a significant factor like adequacy of the laryngeal view is obtained by using laryngoscopy. Aim: The aim of the present study was to “Comparison of endotracheal intubation between C-MAC video laryngoscope and airtraq device” Methodology: The study was performed to compare two different laryngoscopes. 60 ASA physical status I and II non-obese patients of either sex (20-60 yrs age) undergoing general anesthesia for elective surgery were included. Patients with predicted difficult intubation were not included. After obtaining approval from the Institutional Ethical Committee, patients were randomly divided into two groups. Patients of group CM (n=30) were intubated using a C-MAC video laryngoscope, and group AT (n=30) were intubated using Airtraq laryngoscope size 3. Blinding of the attending laryngoscopists was not possible as the two laryngoscopes were conspicuously different. The two optical intubation devices, the Airtraq and C-MAC, were compared with each other with respect to the intubation time, peri laryngoscopy, and intubation changes in heart rate and blood pressure, Modified Cormack and Lehane grading, ease of insertion and incidence of oral trauma during laryngoscopy. The incidence of successful intubation was 100% with both C-MAC video laryngoscope and Airtraq laryngoscope. Results: In Group CM, ease of insertion of CMAC video laryngoscope was very easy in 28 patients and easy in 2 patients. In Group AT, ease of insertion of Airtraq laryngoscope was very easy in all the patients. There was no significant difference during the ease of insertion between both groups. The duration of intubation was significantly less with C-MAC video laryngoscope as compared to Airtraq laryngoscope (15.43±3.08 secs vs. 17.30±2.78secs). Airtraq laryngoscope required a slightly higher time to intubate. In both groups, there was a significant increase in heart rate from pre-intubation value to 1-minute post-intubation value, and the increase was higher with the Airtraq group compared to the C-MAC group. Heart rate in both the group reached its baseline value within 5 minutes after intubation. In both groups, there was a significant increase in the SBP, DBP MAP at 1 minute after intubation. However, the values reached near or even below the baseline at 3 and 5 min intervals. Conclusion: C-MAC video laryngoscope had a slight edge over Airtraq laryngoscope in the aspect of time required for the laryngoscopy and intubation and in offering a better view of glottis and the upper airway.